Longitudinal Shear Flow at the Support Area of Beam with an Overhanging Cantilever - Odrobinak, Jaroslav; Jutila, Aarne (Communications - Scientific letters of the University of Zilina, 2002)
The paper deals with longitudinal shear flow of beams near the support area. Special interest is focused on the overhanging part, which exists in all kinds of beams irrespective of material and span. A parametric study on shear stress distribution at several horizontal height levels by using FEM is presented. Special emphasis is paid to the cantilever length. Finally, conclusions for practical applications are summarized.